2009
DOI: 10.1161/circulationaha.108.846634
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Deficit of SK3 and IK1 Channels Disrupts the Endothelium-Derived Hyperpolarizing Factor Vasodilator Pathway and Causes Hypertension

Abstract: Background-It has been proposed that activation of endothelial SK3 (K Ca 2.3) and IK1 (K Ca 3.1) K ϩ channels plays a role in the arteriolar dilation attributed to an endothelium-derived hyperpolarizing factor (EDHF). However, our understanding of the precise function of SK3 and IK1 in the EDHF dilator response and in blood pressure control remains incomplete. To clarify the roles of SK3 and IK1 channels in the EDHF dilator response and their contribution to blood pressure control in vivo, we generated mice de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
246
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 222 publications
(265 citation statements)
references
References 35 publications
17
246
2
Order By: Relevance
“…Indeed, uncoupling of the gap junctions attenuated the acetylcholine-induced hyperpolarization of the underlying smooth muscle, consistent with a direct current flow between cells (10). Recent evidence, using double KCa2.3/ KCa3.1 knock-out mice, demonstrates that KCa3.1 deficiency attenuates the acetylcholine-induced, EDHF-mediated vasodilation, whereas KCa2.3 knock-out impairs the NO-mediated dilation induced by acetylcholine (9). Additionally, KCa3.1 appears to play a critical role in the propagation of the acetylcholine-induced dilation along the arterioles (13).…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…Indeed, uncoupling of the gap junctions attenuated the acetylcholine-induced hyperpolarization of the underlying smooth muscle, consistent with a direct current flow between cells (10). Recent evidence, using double KCa2.3/ KCa3.1 knock-out mice, demonstrates that KCa3.1 deficiency attenuates the acetylcholine-induced, EDHF-mediated vasodilation, whereas KCa2.3 knock-out impairs the NO-mediated dilation induced by acetylcholine (9). Additionally, KCa3.1 appears to play a critical role in the propagation of the acetylcholine-induced dilation along the arterioles (13).…”
mentioning
confidence: 60%
“…Similarly, Kohler and co-workers (8) demonstrated that the targeted knock-out of KCa3.1 in mice resulted in an attenuated endothelium-derived hyperpolarizing factor (EDHF) 2 response and mild arterial hypertension. Recent studies using mice deficient in both KCa2.3 and KCa3.1 have confirmed the critical role these channels play in the EDHF response and hence blood pressure regulation (9).…”
mentioning
confidence: 93%
“…The underlying hyperpolarization is generated by two subtypes of K Ca channels found in the EC, but not SMC, membrane, the small (SK Ca ,K Ca 2.3) and intermediate (IK Ca, K Ca 3.1) conductance forms that may be activated independently of each other (3). The physiological importance of independent activation is apparent from studies with K Ca 3.1-deficient mice in which the mean blood pressure is raised by ∼7 mmHg, but further elevated by disrupting both K Ca channels (4). In mesenteric resistance arteries, IK Ca channels are focused within EC projections through the internal elastic lamina (IEL) termed myoendothelial junctions (MEJs).…”
mentioning
confidence: 99%
“…[23][24][25] In contrast, K Ca 3.1 channels in endothelial cells and cells of the immune system, such as T-lymphocytes, are activated by more global Ca 2C signals like Ca 2C released from intracellular stores or by the refilling influx through store operated Ca 2C channels like transient receptor potential channels (TRPs) and Ca 2C release activated channels (CRAC). 26,27 K Ca 3.1 is a major component of the endothelial derived hyperpolarizing (EDH) response 28,29 and important for cell proliferation and cytokine release in lymphocytes. 27,30,31 Positive Modulation of K Ca 2/K Ca 3.1 Channels…”
Section: Pharmacological Modulation Of Ion Channel Gatingmentioning
confidence: 99%
“…62,63 Mice deficient in K Ca 3.1 and/or K Ca 2.3 exhibit impaired EDH responses and show a~10 mmHg increase in mean arterial blood pressure, 28,29 while SKA-31 lowers blood pressure in normotensive and hypertensive mice as well as in conscious, normotensive dogs. 29,38,64 Since the blood pressure lowering effect of SKA-31 is absent in KCa3.1 ¡/¡ mice and higher doses of SKA-31 induce sedation and lower heart rate through central K Ca 2 channel activation, 65 it seems desirable to identify K Ca 3.1 selective positive gating modulators in order to help investigate whether such compounds could be developed into a new class of endothelial targeted antihypertensives. 63 This objective recently seems to have been achieved with the demonstration that the K Ca 3.1 selective SKA-121 lowers blood pressure in normotensive and hypertensive mice without affecting heart rate.…”
Section: Site(s) Of Actionmentioning
confidence: 99%